Synthesis of isomorphously substituted extra-large pore UTL zeolites - Shamzhy, Mariya V.; Shvets, Oleksiy V.; Opanasenko, Maksym V.; Yaremov, Pavel S.; Sarkisyan, Liana G.; Chlubna, Pavla; Zukal, Arnost; Marthala, Venkata; Hartmann, Martin; Cejka, Jiri (Journal of Materials Chemistry, 2012)
The influence of various synthesis parameters (e. g. gel composition, pH of the reaction mixture, duration of crystallization) on the phase selectivity of zeolite formation in germanosilicate reaction medium in the presence of different three-valent heteroatoms (B, Al, Ga, Fe or In) was systematically studied and compared with a controlled crystallization from pure germanosilicate media. The boundary conditions of the formation of the pure phase of isomorphously substituted extra-large pore zeolite UTL were established. In the presence of 1 mol% of the respective heteroelement in the initial gel the pH borders of UTL formation are found to be 7.5-11.9 for Fe-, 7.8-12.0 for B-, 8.2-11.0 for Ga-, 11.0-12.0 for In-, and 11.3-12.0 for Al-containing reaction mixtures. The maximum concentration of heteroelements in the reaction mixture for the successful synthesis of UTL is 1.5 mol% for Al and Ga, 6 mol% for In, and 13 mol% for B. The size of UTL crystals decreases in the order Al-> In-> Ga-> Fe-z approximate to B-UTL. The nature of isomorphous substituent influences the textural properties (pore size distribution) of the respective UTL zeolites.